A novel electrocautery-enhanced delivery system for one-step endoscopic ultrasound-guided drainage of the gallbladder and bile duct using a lumen-apposing metal stent: a feasibility study - Yoo, Hae Won; Moon, Jong Ho; Jo, Seok Jung; Lee, Yun Nah; Park, Jae Keun; Lee, Tae Hoon; Cha, Sang-Woo; Cho, Young Deok; Park, Sang-Heum; Park, Se Ik; Jeong, Seok; Lee, Don Haeng (Endoscopy, 2020)
Background The use of a lumen-apposing metal stent (LAMS) capable of one-step endoscopic ultrasound-guided transmural drainage (EUS-TD) can increase the effectiveness of the procedure. We evaluated the newly developed electrocautery-enhanced (EC) delivery system with a LAMS for one-step EUS-guided gallbladder drainage (EUS-GBD) or choledochoduodenostomy (EUS-CDS). Methods In the animal experiment, an EC-LAMS was advanced into the gallbladder without prior tract dilation in four pigs. A conventional LAMS was inserted in another four pigs as a control group. After the animal experiment, 17 patients underwent EUS-TD using the EC-LAMS (EUS-GBD in 10 patients, EUS-CDS in 7). The primary outcome was the technical success rate.Results In the animal study, the mean procedure time was significantly shorter in the EC-LAMS group than in the conventional LAMS group. In the human study, the overall technical success rate was 94.1 %, with one EUS-GBD failure. The clinical success rate was 100 %. The overall adverse event rate was 17.6 %.Conclusions One-step EUS-GBD or EUS-CDS using the novel EC-LAMS is a feasible approach that achieves a high success rate and maintains safety.